Family care leave and the reproduction of gender roles: the case of Argentina - Bonavitta, Paola (2022)
Parental leaves are public policies aimed at balancing parenting tasks with formal employment and are considered part of the policies aimed at regulating and intervening in the care work that mostly weighs on women. This article addresses, from an essayistic methodology, the unequal conditions in the distribution of care in Argentina by analyzing current paternity leaves and the debates on hegemonic masculinities. It also emphasizes the recent project for an Integral Care System proposed in Argentina, which would make a difference in patriarchal policies and cultural practices, distributing care work and promoting gender equity.